Dampak Psikologis Pada Ibu Yang Mengalami Kekerasan Dalam Rumah Tangga Pada Masa Kehamilan di Klinik As-Soheh Medika Tahun 2022 - Annisa Nurhayati Hidayat (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
The number of domestic violence in Serang Regency in 2019 was 102 cases. Around 60.6% of pregnant women are at risk of experiencing violence compared to women who are not pregnant (Ministry of Health, 2019). Preliminary data for pregnant women from the As-Soheh Medika clinic in 2022 reached 360 and the average patient for pregnant women was 30 people in 2022. Data for September - December 2022 for pregnant women at the As-Soheh Medika clinic, 100 pregnant women.The method used in this study is to use a quantitative correlation approach. The sample for this study was 30 samples of pregnant women who experienced domestic violence during September - December 2022. The analysis used was univariate and bivariate with chi-square. Results: The incidence of physical violence was 4%, economic violence was 31.33%, psychological violence was 30.67% and psychological impact was 21%. The method used is univariate analysis in the form of a frequency distribution. There is a significant relationship between the psychological impact and the incidence of domestic violence in pregnant women with a P value of 0.00001 for physical violence, a P value of 0.01 for economic violence, and a P value of 0.003 for psychological violence. Conclusion: The most dominant incidence of domestic violence among pregnant women at the As-Soheh Medika Clinic in 2022 is economic violence at 31.33%. Psychological violence is 30.67% and physical violence is 4%. The number of events that experience psychological impact on pregnant women at the As-Soheh Medika Clinic in 2022 is 21%. There is a significant relationship between psychological impact and physical violence (p value 0.00001), economic violence (p value 0.01) and psychological violence (p value 0.003) for pregnant women at the As-Soheh Medika Clinic in 2022.